METHOD FOR PRODUCING BIOSUPERPHOSPHATE FERTILIZERS CONTAINING HUMIC COMPOUNDS - Arslanov, Akmaljon; Oribzhonov, Mukhammadali; Bektemirov, Azizbek; Azizov, Vokhidkhuja (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The purpose of the research is to develop effective technologies for the production of complex mineral fertilizers enriched with calcium, sulfur, phosphorus, nitrogen, sulfur, and humic compounds. To conduct the experiments, ground phosphate raw materials, gypsum (CaSO4•2H2O), sulfur, urea, and leonardite (total humus content 52.3-64.5%; organic matter 66.7-71.1%; moisture content 26.53-33.07%) were used as starting materials. The research was conducted in a glass reactor equipped with a vane stirrer and placed in a thermostated container. In a thermostated beaker, ground phosphate raw materials, gypsum (CaSO4•2H2O), sulfur, urea, and leonardite (total humus content 52.3-64.5%) were placed and mixed with water, then the resulting suspension was intensively stirred for 10 minutes at 70-80°C. The pulp was dried to constant weight at 100-105oC. In this case, a product is obtained (in mass. P2O5 total. = 17.9; P2O5 sol. = 6.37; P2O5 p.s. = 6.01; Nover. = 1; CaO total = 34.0; CaO p = 10.0; MgO = 1.4; SO3total. = 11.35; SO3p.p. = 2.0; Total organic matter = 8.0; PH=7.28 and others.